Active noise control methods in Poland - Zawieska, W. M. (Archives of Acoustics, 2004)
The article presents the development and selected uses of methods of active noise reduction in Poland: from the first theoretical studies of Prof. Wojciech Rubinowicz to the latest study with the use of neural networks. The article discusses the principles of active compensation of sound. It also presents the results of Polish research centres’ work on the use of active systems for reducing noise in ducts, power transformers: noise and to improve hearing protectors parameters.